Normalization of coagulopathy is associated with improved outcome after isolated traumatic brain injury. (July 2016) - Epstein, Daniel S.; Mitra, Biswadev; Cameron, Peter A.; Fitzgerald, Mark; Rosenfeld, Jeffrey V.
Highlights: Normalization of international normalized ratio (INR) was associated with improved mortality in acute traumatic coagulopathy (ATC) patients in the setting of isolated traumatic brain injury (iTBI). There was substantial lag time between product delivery and eventual coagulation normalization. Specific management of coagulopathy should be implemented as early as possible. Abstract: Acute traumatic coagulopathy (ATC) has been reported in the setting of isolated traumatic brain injury (iTBI) and is associated with poor outcomes. We aimed to evaluate the effectiveness of procoagulant agents administered to patients with ATC and iTBI during resuscitation, hypothesizing that timely normalization of coagulopathy may be associated with a decrease in mortality. A retrospective review of the Alfred Hospital trauma registry, Australia, was conducted and patients with iTBI (head Abbreviated Injury Score [AIS] ⩾3 and all other body AIS <3) and coagulopathy (international normalized ratio ⩾1.3) were selected for analysis. Data on procoagulant agents used (fresh frozen plasma, platelets, cryoprecipitate, prothrombin complex concentrates, tranexamic acid, vitamin K) were extracted. Among patients who had achieved normalization of INR or survived beyond 24 hours and were not taking oral anticoagulants, the association of normalization of INR and death at hospital discharge was analyzed using multivariable logistic regression analysis. There were 157 patients with ATC of whom 68 (43.3%) received procoagulant products within 24 hours of presentation. The median time to delivery of first products was 182.5 (interquartile range [IQR] 115–375) minutes, and following administration of coagulants, time to normalization of INR was 605 (IQR 274–1146) minutes. Normalization of INR was independently associated with significantly lower mortality (adjusted odds ratio 0.10; 95% confidence interval 0.03–0.38). Normalization of INR was associated with improved mortality in patients with ATC in the setting of iTBI. As there was a substantial time lag between delivery of products and eventual normalization of coagulation, specific management of coagulopathy should be implemented as early as possible.